Palladium nanoparticles in polymer as electrocatalysts - N. A. Yashtulov; A. N. Bolshakova; V. R. Flid; A. A. Revina (Тонкие химические технологии)
Palladium nanoparticles were synthesized on and in Nafion polymeric film by radiation-chemical reduction in reverse micelles solution. The effect of solubilization degree and water drop size on the nanoparticles formation is shown.